Web-based promotional media in enhancing customer engagement in the digital age - Antoni Steven; Novi Hendri Adi (Researcher and Lecturer Society, 2024)
Coffee Shop faces challenges in marketing its products and needs a corporate website that can showcase its profile, products, and online ordering services to increase customer affordability and convenience. The business still relies on social media, WhatsApp, and phone calls to conduct transactions, which often confuses potential buyers and reduces their interest in purchasing the products. To overcome this problem, research was conducted to design and implement an effective website as a promotional and informational tool. The website was developed with a database programming base using the waterfall system design method, following five main stages: requirements analysis, system design, program code writing, program testing, and program implementation. The Unified Modeling Language (UML) selection as a modeling tool ensures that the system analysis and design are well structured. The results of this research include four diagrams and six tables that support the structure and functionality of the website. The website was tested using the black box testing method on a local server, with results showing that the system successfully promoted and provided detailed information to potential customers. The available search function allows customers to easily search for products based on keywords, making ordering more efficient.